The gendered worlds of Latin American women workers : from household and factory to the union hall and ballot box - French, John D.; James, Daniel, 1948- (Comparative and international working-class history., 1997)
"Collection of well-researched articles effectively combines gender history and labor history and includes specialized studies of Argentina, Brazil, Chile, Colombia, and Guatemala. Each article is thoroughly footnoted, revealing broadly-based sources including interviews, memoirs, and government publications, as well as authors' extensive reading in comparable published studies and theoretical literature. Editors also contribute introductory and concluding essays rich in historiographical and methodological insights"--Handbook of Latin American Studies, v. 58.